Transforming food systems: Multi-stakeholder platforms driven by consumer concerns and public demands - Herens, Marion C.; Pittore, Katherine H.; Oosterveer, Peter (Elsevier, 2022)
Food systems governance for healthy and sustainable diets remains a challenge. New structures are needed to better connect food systems actors. This paper argues that existing multi-stakeholder platforms (MSPs) have the potential to contribute to food systems governance by facilitating linkages between actors and scales. In a non-experimental study existing MSPs (n = 89) were explored in four countries addressing food and nutrition security. A diagnostic framework was used to identify MSP's capacities to address governance principles like system-based problem framing, boundary spanning, adaptability, inclusiveness, and transformative capacity. Existing MSPs can play a role in spanning boundaries, thereby increasing adaptability and learning, but seem less promising in shifting to systems-based narratives and thus may have limited capacity to truly transform food